Near term premature births, its is possible to establish viability limits? - Grzona, María Estela (Acta Bioethica, 2006)
Near term premature birth is one of the frequent situations in ethical decision making related to neonatology. Is there a weight limit or a gestational age under which it should not be initiated or added life saving therapies because of being considered futile for the child, prolonging his/her life without hope, making patient and family to suffer and occupying a unit depriving of health care to another child with greater surviving probability? The neonatal score risk allows to predict whether the seriously ill premature can be recovered or not, allowing to take ethical decisions based on a validated technique, which allows to act for the greatest benefit for the child and family, and at the same time resources are used more equitably.